Strategi Pendidikan Karakter untuk Membentuk Sikap Tanggung Jawab Pada Siswa Sekolah Dasar - Menik Anggun Cintyani; Khofifatul Azma; Muhammad Alif Syairudin; Muhammad Nofan Zulfahmi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study is a form of character education strategy analysis to form responsible elementary school students through a literature study approach. The data for this study were obtained from a literature review including books, academic journals and previous research related to classroom management and how students' characters are formed. The results of this study explain that effective character education strategies include the development of participatory rules, the application of consistent consequences, and rewards for positive behavior. This approach helps students understand the importance of personal and social responsibility to support the creation of a conducive learning environment. This study provides a conceptual contribution to the development of classroom management strategies as an integral part of character education in elementary schools.